IDEALISM AND GENDER IN MODERATING LOVE OF MONEY, MACHIAVELLIANISM, AND EMPLOYEES’ ETHICAL PERCEPTION IN BUSINESS (Accounting Sample) - Tan, Thalia Margareta; Hajanirina, Andrianantenaina; Reyes, Mila Austria (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This research aims to analyze key traits and attitudes that business practitioners, entrepreneurs, or anyone working in an organization possess, influencing their daily management and long-term practices that may even cause unexpected result like financial scandals. International financial scandals (like Enron and WorldCom) and national ones (such as Garuda and Jiwasraya) highlight the severe consequences of unethical practices, often resulting in substantial financial losses. Using questionnaire survey, SEM analysis is conducted to test the traits among accountants from Public Accounting Firms sampled as 269 respondents. The result reveals that while love of money does not significantly affect employees' ethical perceptions, Machiavellianism has a negative impact, which can be mitigated by idealism. Gender showed minimal influence on moderating these effects. The findings also emphasize the importance of moral development in the accounting profession, suggesting that fostering ethical reasoning is more effective than simply following regulations.